METHODOLOGY FOR DEVELOPING THE CREATIVITY OF THE SENIOR CLASS TEACHER - Dilrabo AKHMEDOVA (Scholar Express Journal, 2023)
Article Ethnopedagogy of creativity of senior class teacher using about the development methodology, the possibilities of preparing senior class teachers for innovative activities based on creative ability, and the forms, methods and technologies of improving the senior class teacher's creativity development methodology written
Keywords: logical thinking; development; heuristic ability